KENAL DIRI SECARA QUR’ANI MELALUI PROSES TERCIPTANNYA MANUSIA SEBAGAI MODAL PENGUATAN KARAKTER - Khususiyah, Khususiyah (Universitas Nusantara PGRI Kediri, 2018)
Knowing the Qur'anic self through the process of human creation is a very simple and fundamental way of reinforcing individual character. Thus, the key concept in writing this article is to know yourself in the Qur'an. With the hope of knowing themselves in the Qur'an will understand each in-dividu in order to be able to portray and position themselves well and correctly (character). As it is written in the Holy Qur'an (Surat 51: 21) which means,